Odpowiedzi

2010-03-24T17:29:38+01:00
A)
4² + 4² = x²
x² = 32
x = 4√2

l = 2*4 + 4√2
l = 4(2 + √2)

b)
a² + a² = 4²
2a² = 16 /:2
a² = 8
a = 2√2
l = 2 * 2√2 + 4
l = 4√2 + 4
l = 4(√2 + 1)

c)
(√3/2)² + (√3/2)² = x²
x² = 3/4 + 3/4
x² = 6/4
x = √6/2
l = 2√3/2 + √6/2
1 5 1
2010-03-24T17:34:14+01:00
A)
4² + 4² = x²
x² = 32
x = 4√2

l = 2*4 + 4√2
l = 4(2 + √2)

b)
a² + a² = 4²
2a² = 16 /:2
a² = 8
a = 2√2
l = 2 * 2√2 + 4
l = 4√2 + 4
l = 4(√2 + 1)

c)
(√3/2)² + (√3/2)² = x²
x² = 3/4 + 3/4
x² = 6/4
x = √6/2
l = 2√3/2 + √6/2
1 1 1